Awareness of Mental Health Challenges and its Implications for Job Performance among Library Staff at the Workplace: A Qualitative Study - Kyumana, Valeria (University of Dar es Salaam Library Journal, 2022)
Mental health is one of the neglected aspects at the workplace during planning and policy formulation that, in turn, affects job performance. This study, aimed to investigate awareness of mental health challenges among library staff at the Institute of Finance Management (IFM), Tanzania and their implications for job performance. Using a pragmatic qualitative research approach, the study conducted four FGDs coupled with interviews to collect data from library staff and heads of department and the head of the library. The resultant data was subjected to content relational analysis and findings were organised thematically. Findings revealed that most of the library staff had low awareness of mental health challenges such as depression, anxiety, stress and addictive behaviours but were familiar with symptoms such as extreme sadness, lack of will to do anything and constant fear. Stigma, lack of education and professional counsellors at the workplace and lack of management support emerged as major hindrances to maintaining a positive mental health. Availability of counsellors to help staff deal with life ' s challenges and navigate through personal problems; provision of education to reduce social stigma and honest conversations regarding mental health challenges were recommended as prerequisite for better mental health of library staff.